Left atrial appendage occlusion in vulnerable oldest-old patients: effectiveness and safety in a large single-center registry - Fastner, Christian; Tavas, Enise; Hetjens, Svetlana; Kruska, Mathieu; Ansari, Uzair; Behnes, Michael; Kuschyk, Jürgen; Dürschmied, Daniel; Burkhardt, Heinrich; Alonso, Angelika; Akın, Ibrahim (Journal of the neurological sciences, 2025)
Background and aim - Complex periprocedural approaches contrast with the need of oldest-old patients to keep medical procedures simple and short. This study investigates the effectiveness and safety of a simplified non-complex LAAO procedure. - Methods - All patients who received an LAAO procedure at our center since 2014 with available follow-up data were retrospectively assessed concerning effectiveness in preventing all-cause death, stroke, or systemic embolism (i.e., effectiveness outcome). Safety was primarily evaluated by major bleeding (i.e., ≥ BARC type 3). Oldest-old patients (i.e., ≥ 80 years of age) were compared with younger patients. - Results - 43.0 % of 230 patients were oldest-olds. High technical success rate was achieved in both groups (oldest-olds 96.0 vs. younger patients 98.5 %; p = 0.41). Major complications occurred in 8.1 vs. 3.8 % of patients (p = 0.17). Effectiveness outcome was achieved in 70.7 vs. 82.4 % of patients (p = 0.035; mean follow-up 428 (100; 1007) and 382 (179; 1192) days). Oldest-old patients trended to an excess mortality (22.2 vs. 13.0 %; p = 0.064) and more ischemic strokes (10.1 vs. 3.8 %; p = 0.056). This was not associated with peri-device leaks ≥ 5 mm or device-related thromboses (2.0 vs. 1.5 %; p = 1.00). Major bleeding occurred in 9.1 vs. 7.6 % of patients over total follow-up (p = 0.69). - Conclusions - Non-complex LAAO procedure achieved a state-of-the-art technical success rate and a low complication rate in vulnerable oldest-old patients. Care should be taken to identify patients with sufficient life expectancy to benefit from LAAO. The trend towards more ischemic strokes during follow-up is an important signal focusing on cardioembolic stroke etiologies besides LAA thrombi in these patients.
Online verfügbar: 28. April 2025, Artikelversion: 9. Mai 2025
Gesehen am 25.09.2025